Inter‐Relations between Partner‐Provided Support and Self‐Efficacy: A Dyadic Longitudinal Analysis. Issue 3 (24th June 2019) - Hohl, Diana Hilda; Schultze, Martin; Keller, Jan; Heuse, Silke; Luszczynska, Aleksandra; Knoll, Nina
Abstract : Background: Existing evidence indicates that social support may enhance recipients' self‐efficacy (enabling hypothesis) or that self‐efficacy facilitates support receipt (cultivation hypothesis). However, less is known about the time‐lagged support–self‐efficacy relationship in couples. Our aim was to disentangle reciprocal interrelations among stable and time‐varying components of support provision and self‐efficacy in couples over time. Methods: We conducted secondary analyses of a published randomised controlled trial with six assessments, spanning 1 year and N  = 338 heterosexual couples (age range: 18–80 years). Women's and men's reports on physical activity‐specific provided support and physical activity‐specific self‐efficacy were analysed. Results: Based on the actor‐partner interdependence model, we compared nested random intercepts cross‐lagged panel models. The final model revealed no gender effects. Stable levels of both partners' support provision and self‐efficacy were positively associated. At the time‐varying level, one partner's self‐efficacy predicted the other partner's support provision later on. No lagged‐association emerged for the opposite predictive direction. Conclusions: Partners' stable shares of provided support and self‐efficacy were interrelated, whereas higher time‐varying self‐efficacy of one partner seemed to activate support provision from the other partner, confirming the cultivation hypothesis but not the enabling hypothesis.